Determinants that Affect Females' Attitudes Toward Online Shopping in the Western Region of Saudi Arabia. Issue 7 (25th July 2022) - Alshehri, Manal Saeed; Ali, Noor Azman; Sidek, Shafie; Hwa, Jacky Cheah Jun
No abstract available